DIFFERENCES BETWEEN BANNER AND LEAFLET EDUCATION IN STUDENTS' ORAL HEALTH KNOWLEDGE: CROSS-SECTIONAL STUDY - Riski Amalia Hidayah; Fitri Diah Oktadewi; Elisa Astuty Miniarny; Atha Priandha; Kezia Rastya Mitzi Lael Muskitta; Haris Budi Widodo (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: The prevalence of dental caries in children in Banyumas Regency is increasing. Karanglewas Public Health Centre is the only Health Center in Banyumas Regency that regularly performs periodic examinations in nearby primary schools. However, some schools still report a high prevalence of dental caries, reaching approximately 91.3% at SDN 1 and 2 Tamansari. Improving knowledge through oral health counseling is essential, banners and leaflets provide engaging educational overviews, which are suitable for children aged 7 to 8 years old. Purpose: To compare the effectiveness of banner-based and leaflet-based counseling in improving oral health knowledge among second-grade students at SDN 1 and 2 Tamansari. Method: This cross-sectional study used a pre-experimental, pre-post test design. This research used total sampling. 71 students participated classified into 32 in the banner counseling group and 39 in the leaflet counseling group. The Wilcoxon test analyzed knowledge score changes in the leaflet group and the Paired-T test in the banner group. An Independent-T test compared both media. Result: Knowledge improved significantly from pre-to post-counseling in both groups (p-value < 0.05). The increase in knowledge scores also differed significantly between the two media (p-value < 0.05), with the leaflet group showing a greater increase (37.54 ± 17.35) than the banner group (12.13 ± 6.22). Conclusion: Both media improved students’ oral health knowledge, but leaflets were more effective than banners.